2011
DOI: 10.1017/s0033291711001528
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying domains of internalizing psychopathology using neurophysiology

Abstract: Current initiatives such as the National Institute of Mental Health's Research Domain Criteria project aim to reorganize classification of mental disorders along neurobiological lines. Here, we describe how consideration of findings from psychiatric research employing two physiological measures with distinct neural substrates--the startle blink reflex and the error-related negativity (ERN)--can help to clarify relations among disorders entailing salient anxiety or depressive symptomatology. Specifically, findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 102 publications
3
65
0
2
Order By: Relevance
“…One of the most robust findings in the error monitoring literature is an enhanced ERN/Ne component in participants with high trait negative affect (see Moser et al, 2013;Olvet and Hajcak, 2008;Simons, 2010;Vaidyanathan et al, 2012). Using standard interference tasks, several ERP studies have reported greater ERN/Ne (and often CRN) components in patients with anxiety or internalizing disorders (Krueger et al, 2001), including obsessive compulsive disorders (Carrasco et al, 2006;Endrass et al, 2008;Endrass et al, 2010;Gehring et al, 2000;Hajcak and Simons, 2002;Johannes et al, 2001;Stern et al, 2010), depression (Aarts et al, in press), and generalized anxiety disorders (Weinberg et al, 2010).…”
Section: Evidence From Individual Differences and Psychopathologymentioning
confidence: 99%
“…One of the most robust findings in the error monitoring literature is an enhanced ERN/Ne component in participants with high trait negative affect (see Moser et al, 2013;Olvet and Hajcak, 2008;Simons, 2010;Vaidyanathan et al, 2012). Using standard interference tasks, several ERP studies have reported greater ERN/Ne (and often CRN) components in patients with anxiety or internalizing disorders (Krueger et al, 2001), including obsessive compulsive disorders (Carrasco et al, 2006;Endrass et al, 2008;Endrass et al, 2010;Gehring et al, 2000;Hajcak and Simons, 2002;Johannes et al, 2001;Stern et al, 2010), depression (Aarts et al, in press), and generalized anxiety disorders (Weinberg et al, 2010).…”
Section: Evidence From Individual Differences and Psychopathologymentioning
confidence: 99%
“…The two factors function as the main pathways for lifetime comorbidity, persistence of disorders, and familial transmission of psychopathology (Eaton et al, 2013b;Kessler et al, 2011;Starr, Conway, Hammen, & Brennan, 2014). In line with initiatives such as RDoC (Caspi et al, in press;Insel, et al, 2010), and in light of their properties and links with genetic and neurobiological substrates of behavior (Kendler et al, 2011;Vaidyanathan, Patrick, & Cuthbert, 2009;Vaidyanathan, Nelson, & Patrick, 2012), these sources of transdiagnostic disorder variance and comorbidity are becoming a growing focus of scientific inquiry and clinical intervention (e.g., Barlow et al, 2011;Barlow et al, 2014;Rodriguez-Seijas, Eaton, & Krueger, in press). …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In a follow up study, Vaidyanathan, Nelson, and Patrick (2012) applied the same strategy to another index of neurophysiology, the ERN (an event-related potential waveform sensitive to error commisThis document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Connecting Mechanisms To Palpable Psychopathologymentioning
confidence: 99%